The role of Hydrogel Centella asiatica in the Inflammatory phase of cuts in male rats - Indah Nur Imamah (Jurnal Ilmu Kesehatan, 2020)
Abstract: The inflammatory phase occurs immediately after injury and is a very important phase in the wound healing process. Inflammation is a determining phase of whether the wound healing process can continue without prolonged infection, so optimal efforts are needed in wound care so that the wound healing process can run well according to the four phases of healing. This research is a true experimental study with a post-test-only control group design approach. The sampling method used was a randomized control group pre-post-test design of 12 individuals. The statistical test results obtained a p-value = 0.004 which means that at 5% alpha there is a significant difference in the number of leukocytes between the intervention group and the control group. The content of Centella asiatica that plays a role in the inflammatory phase were essential oil and triterpenoid saponins.